NLRP3-mediated pyroptosis in diabetic nephropathy - Jiayi Wan; Jiayi Wan; Jiayi Wan; Jiayi Wan; Dongwei Liu; Dongwei Liu; Dongwei Liu; Dongwei Liu; Shaokang Pan; Shaokang Pan; Shaokang Pan; Shaokang Pan; et al. (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is the main cause of end-stage renal disease (ESRD), which is characterized by a series of abnormal changes such as glomerulosclerosis, podocyte loss, renal tubular atrophy and excessive deposition of extracellular matrix. Simultaneously, the occurrence of inflammatory reaction can promote the aggravation of DN-induced kidney injury. The most important processes in the canonical inflammasome pathway are inflammasome activation and membrane pore formation mediated by gasdermin family. Converging studies shows that pyroptosis can occur in renal intrinsic cells and participate in the development of DN, and its activation mechanism involves a variety of signaling pathways. Meanwhile, the activation of the NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome can not only lead to the occurrence of inflammatory response, but also induce pyroptosis. In addition, a number of drugs targeting pyroptosis-associated proteins have been shown to have potential for treating DN. Consequently, the pathogenesis of pyroptosis and several possible activation pathways of NLRP3 inflammasome were reviewed, and the potential drugs used to treat pyroptosis in DN were summarized in this review. Although relevant studies are still not thorough and comprehensive, these findings still have certain reference value for the understanding, treatment and prognosis of DN.